2022
DOI: 10.3390/ijerph19116881
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Treatment of Patients with Colorectal Cancer

Abstract: Colorectal cancer is one of the most common cancers in Europe and the world. Cancer treatments have side effects and cause significant deterioration of the patient’s nutritional status. Patient malnutrition may worsen the health condition and prevent the deliberate effects of the therapy. The aim of this review was to describe the available data about clinical nutrition in colorectal cancer patients. A large proportion of colorectal cancer patients suffer from malnutrition, which negatively affects the surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…To date, some notable progress has been made in this area [ 66 ]. As an essential micronutrient in foods and mineral supplements, zinc has been examined in many clinical trials for the possible prevention of gynecological cancers [ 64 ], like breast [ 26 ] and ovarian cancers [ 65 ], gastrointestinal and hepatic cancers [ 67 , 68 , 69 , 70 ], and lung [ 71 ] and oral cancers [ 72 ], in addition to cardiovascular disease (CVD) [ 73 , 74 ]. However, if breast cancers sequester and use more zinc than normal cells, therapeutic use of an excessive amount of zinc needs to be examined in animal models before any attempt at clinical trials for cancer treatment.…”
Section: Zinc and The Cmpn/cmp Signaling Networkmentioning
confidence: 99%
“…To date, some notable progress has been made in this area [ 66 ]. As an essential micronutrient in foods and mineral supplements, zinc has been examined in many clinical trials for the possible prevention of gynecological cancers [ 64 ], like breast [ 26 ] and ovarian cancers [ 65 ], gastrointestinal and hepatic cancers [ 67 , 68 , 69 , 70 ], and lung [ 71 ] and oral cancers [ 72 ], in addition to cardiovascular disease (CVD) [ 73 , 74 ]. However, if breast cancers sequester and use more zinc than normal cells, therapeutic use of an excessive amount of zinc needs to be examined in animal models before any attempt at clinical trials for cancer treatment.…”
Section: Zinc and The Cmpn/cmp Signaling Networkmentioning
confidence: 99%
“…In this study loss of appetite found to be a challenge to colorectal cancer patient as it lead to poor prognosis of the patient status and effect on cancer therapy given by health care providers. Similarly to study done by (Lewandowska et al, 2022) found that people who have extremely low appetites for longer than a few days typically lose weight. People who lose weight because they don't eat enough frequently experience weakness and exhaustion.…”
Section: Discussionmentioning
confidence: 57%
“…Consuming dietary ber may help slow down the development of colorectal cancer in addition to consuming micronutrients, as shorter intestinal transit times indicate a shorter persistence of dietary carcinogens in the lumen. The increase in fecal volume is also connected to the protective action of the bers (Lewandowska et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Individualised nutritional intervention that focuses on increased nutrient demand in both patients and survivors of CRC is essential. (1,2,10,11) Guidelines 1. The International Agency for Research on Cancer (IARC) has classified red meat as Group 2A: substances probably carcinogenic to humans.…”
Section: Colorectal Cancer Backgroundmentioning
confidence: 99%